Updated French guidelines for diagnosis and management of pelvic inflammatory disease. Issue 2 (August 2016) - Brun, Jean-Luc; Graesslin, Olivier; Fauconnier, Arnaud; Verdon, Renaud; Agostini, Aubert; Bourret, Antoine; Derniaux, Emilie; Garbin, Olivier; Huchon, Cyrille; Lamy, Catherine; Quentin, Roland; Judlin, Philippe; et al.
Abstract: Background: Pelvic inflammatory disease (PID) is commonly encountered in clinical practice. Objectives: To provide up-to-date guidelines on management of PID. Search strategy: An initial search of the Cochrane database, PubMed, and Embase was performed using keywords related to PID to identify reports in any language published between January 1990 and January 2012, with an update in May 2015. Selection criteria: All identified reports relevant to the areas of focus were included. Data collection and analysis: A level of evidence based on the quality of the data available was applied for each area of focus and used for the guidelines. Main results: PID must be suspected when spontaneous pelvic pain is associated with induced adnexal or uterine pain (grade C). Pelvic ultrasonography is necessary to exclude tubo-ovarian abscess (grade B). Microbiological diagnosis requires vaginal and endocervical sampling for molecular and bacteriological analysis (grade B). First-line treatment for uncomplicated PID combines ofloxacin and metronidazole for 14 days (grade B). Treatment of tubo-ovarian abscess is based on drainage if the collection measures more than 3 cm (grade B), with combined ceftriaxone, metronidazole, and doxycycline for 14–21 days. Conclusions: Current management of PID requires easily reproducible investigations and treatment, and thus can be applied worldwide.